Purification of biodiesel from crude palm oil using multistage portable fixed bed adsorber - Mohammad Prasanto Bimantio; Herawati Oktavianty; Reza Widyasaputra (Institution for Industrial Research and Standardization of Industry - Padang, 2022)
Crude biodiesel needs to go through purification process, to meet international biodiesel specifications.. The widely used adsorption column is in the form of a fixed bed column, where the contents of the column are stacked in a mess. This makes the adsorbent difficult to clean and fill, and irregular adsorbent accumulation can hinder the flow of the fluid to be purified. In this study, an adsorption column with a portable circulation system used to observe the influence of circulation and adsorption level on the purity of biodiesel. Main equipment of this research is a portable adsorption biodiesel purification device. The column consists of: top distributor, packed bed and bottom collector. The tool is made of 3D printed polymer material. At the bottom of the tower there is a buffer tank and a pump for circulating the biodiesel to be purified. The results showed that some analytical parameters based on the results of t-test, namely: density, acid value, saponification and yellowish-blue tendency, there are significant differences between the results before and after purification. For all the parameters analyzed in this study, the number of stages and fluid circulation gave significantly different results. The results of methyl ester analysis confirmed this, where the more cycles in the column, the higher the methyl ester peak produced. As number of cycles in the adsorption column increases, peak area of the methyl ester produced becomes wider, which can be explained by the ability of column and its packing materials to filter impurities present in column.